The Role of Green Brand Image Awareness and Environmental Awareness on Purchasing Decisions by Controlling the Behavior of Potential Consumers of the Body Shop Mojokerto - Baiqun Isbahi, Muhammad; Kartika Pertiwi, Tri; Purwanto, Sugeng (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The purpose of this study is to investigate the role of environmental knowledge and green brand image awareness in motivating green product purchasing decisions. The purpose of this study is to ascertain the impact of environmental knowledge and green brand image awareness on purchase decisions, both directly and indirectly via behavioral control. The population in this study is 220 potential The Body Shop Mojokerto customers, with the sample used being the younger generation in Mojokerto who are familiar with The Body Shop and are potential customers. The sample in this study falls under the purposive sampling category, with a total sample size of 120 respondents. The descriptive analysis and Partial Least Square (PLS) methods were utilized, with the SmartPLS version 3.0 software application. The study's findings indicate that environmental awareness is vital for improving purchase decisions, as well as the findings of an indirect association via behavioral control. According to these findings, behavioral control is referred to as mediation. Furthermore, understanding of the green brand image is crucial, as it is capable of encouraging positive behavioral control, which can impact purchase decisions.